2008
DOI: 10.1007/s11239-007-0191-9
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin after cardiac surgery: implications on short and mid-term outcome

Abstract: Low AT after cardiac surgery is associated with higher incidences of peri-operative complications and worse survival in the mid-term. Future studies should clarify the pathophysiologic mechanism of this findings and possible therapeutic directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…8 During these surgeries, the levels of AT activity decrease owing to consumption 9 and to hemodilution, 10 resulting in a deficient amount of this protein at the end of the procedure, 11,12 which has been associated with a worse clinical recovery after surgery. [13][14][15] Furthermore, in these studies, the patients with low levels of AT activity after CS remained in the ICU longer, with mechanical ventilation, and required more surgical re-explorations and blood transfusions. 14, 15 Paparella et al 14 showed that, after being admitted to the ICU, patients with AT activity levels Ͻ63.7% had a much greater incidence of adverse cardiac events, such as excessive bleeding, infections, stroke, acute renal failure, sepsis, and atrial fibrillation.…”
Section: Uring the Past 2 Decades Cardiac Surgery (Cs)mentioning
confidence: 94%
See 4 more Smart Citations
“…8 During these surgeries, the levels of AT activity decrease owing to consumption 9 and to hemodilution, 10 resulting in a deficient amount of this protein at the end of the procedure, 11,12 which has been associated with a worse clinical recovery after surgery. [13][14][15] Furthermore, in these studies, the patients with low levels of AT activity after CS remained in the ICU longer, with mechanical ventilation, and required more surgical re-explorations and blood transfusions. 14, 15 Paparella et al 14 showed that, after being admitted to the ICU, patients with AT activity levels Ͻ63.7% had a much greater incidence of adverse cardiac events, such as excessive bleeding, infections, stroke, acute renal failure, sepsis, and atrial fibrillation.…”
Section: Uring the Past 2 Decades Cardiac Surgery (Cs)mentioning
confidence: 94%
“…[13][14][15] Furthermore, in these studies, the patients with low levels of AT activity after CS remained in the ICU longer, with mechanical ventilation, and required more surgical re-explorations and blood transfusions. 14, 15 Paparella et al 14 showed that, after being admitted to the ICU, patients with AT activity levels Ͻ63.7% had a much greater incidence of adverse cardiac events, such as excessive bleeding, infections, stroke, acute renal failure, sepsis, and atrial fibrillation.…”
Section: Uring the Past 2 Decades Cardiac Surgery (Cs)mentioning
confidence: 94%
See 3 more Smart Citations